Perlindungan Terhadap Masyarakat Yang Tinggal Di Sekitar Tower Telekomunikasi Menurut Hukum Ekonomi Syariah - Iskandar Iskandar (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2021)
The presence of towers in the present era is needed to expedite the communication network. However, its existence has sparked various polemics and unrest among the public regarding legal protection and public safety due to the impact of the telecommunication tower. In sharia economic law, humans as individual beings have their respective rights in life, therefore they must receive equal treatment with their position in accordance with their rights. With a case study at Gampong Atuek Cut, Simpang Tiga Subdistrict, Aceh District, Aceh Province, the authors conducted research using an empirical juridical approach, field research, interviews. The result of this research is that the legal protection obtained by the community around the telecommunication tower is in accordance with statutory regulations. Arrangements for joint use of towers have been realized to achieve legal certainty and create uniformity aimed at realizing a comfortable life and sustainable economic development in order to improve the quality of life and the environment.Keywords: Community Protection, Tower, Sharia.